Inbred Mouse Populations Exhibit Intergenerational Changes in Intestinal Microbiota Composition and Function Following Introduction to a Facility - Choo, Jocelyn M.; Trim, Paul J.; Leong, Lex E. X.; Abell, Guy C. J.; Brune, Carly; Jeffries, Nicole; Wesselingh, Steve; Dear, T. N.; Snel, Marten F.; Rogers, Geraint B. (Frontiers in Microbiology, 2017)
Inbred mice are used to investigate many aspects of human physiology, including susceptibility to disease and response to therapies. Despite increasing evidence that the composition and function of the murine intestinal microbiota can substantially influence a broad range of experimental outcomes, relatively little is known about microbiome dynamics within experimental mouse populations. We investigated changes in the intestinal microbiome between C57BL/6J mice spanning six generations (assessed at generations 1, 2, 3 and 6), following their introduction to a stringently controlled facility. Faecal microbiota composition and function were assessed by 16S rRNA gene amplicon sequencing and liquid chromatography mass spectrometry, respectively. Significant divergence of the intestinal microbiota between founder and second generation mice, as well as continuing inter-generational variance, was observed. Bacterial taxa whose relative abundance changed significantly included Akkermansia, Turicibacter and Bifidobacterium (p< 0.05), all of which are recognised as having the potential to substantially influence host physiology. Shifts in microbiota composition were mirrored by corresponding differences in the faecal metabolome (r=0.57, p=0.0001), with notable differences in levels of tryptophan pathway metabolites and amino acids, including glutamine, glutamate and aspartate. The magnitude of these changes in the intestinal microbiota and metabolome characteristics during acclimation were on a scale with those observed between populations housed in separate facilities, which differed in regards to husbandry, barrier conditions and dietary intake. The microbiome variance reported here has major implications for experimental reproducibility, and as a consequence, experimental design and the interpretation of research outcomes across as wide range of contexts.